Comparison of Angiotensin‐Converting Enzyme Inhibitor and Angiotensin Receptor Blocker Management Strategies Before Cardiac Surgery: A Pilot Randomized Controlled Registry Trial. Issue 20 (16th October 2018) - van Diepen, Sean; Norris, Colleen M.; Zheng, Yinggan; Nagendran, Jayan; Graham, Michelle M.; Gaete Ortega, Damaris; Townsend, Derek R.; Ezekowitz, Justin A.; Bagshaw, Sean M.
Abstract : Background: Postoperative clinical outcomes associated with the preoperative continuation or discontinuation of angiotensin‐converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) before cardiac surgery remain unclear. Methods and Results: In a single‐center, open‐label, randomized, registry‐based clinical trial, patients undergoing nonemergent cardiac surgery were assigned to ACEI/ARB continuation or discontinuation 2 days before surgery. Among the 584 patients screened, 261 met study criteria and 126 (48.3%) patients were enrolled. In total, 121 patients (96% adherence; 60 to continuation and 61 to ACEI/ARB discontinuation) underwent surgery and completed the study protocol, and follow‐up was 100% complete. Postoperative intravenous vasopressor use (78.3% versus 75.4%, P =0.703), vasodilator use (71.7% versus 80.3%, P =0.265), vasoplegic shock (31.7% versus 27.9%, P =0.648), median duration of vasopressor (10 versus 5 hours, P =0.494), and vasodilator requirements (10 versus 9 hours, P =0.469) were not significantly different between the continuation and discontinuation arms. No differences were observed in the incidence of acute kidney injury (1.7% versus 1.6%, P =0.991), stroke (no events, mortality (1.7% versus 1.6%, P =0.991), median duration of mechanical ventilation (6 versus 6 hours, P =0.680), and median intensive care unit length of stay (43 versus 27 hours, P =0.420) between the treatment arms. Conclusions: A randomized study evaluating the routine continuation or discontinuation of ACEIs or ARBs before cardiac surgery was feasible, and treatment assignment was not associated with differences in postoperative physiological or clinical outcomes. These preliminary findings suggest that preoperative ACEI/ARB management strategies did not affect the postoperative course of patients undergoing cardiac surgery. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02096406.